1989
DOI: 10.1103/physrevb.39.11345
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin rotation in the magnetic and superconducting ground states of (U,Th)Be13and (U,Th)Pt3<

Abstract: Microscopic aspects of magnetism and superconductivity have been studied in the heavy-fermion superconducting alloy systems (U,Th)Be» and (U,Th)Pt3 using the technique of positive-muon (p ) spin rotation and relaxation (pSR). In U& Th Be», x =0.033, a striking increase of zero-field Kubo-Toyabe relaxation rate o. KT is observed below the temperature T,2-0.4 K at which a second phase transition occurs in the superconducting state. This jump is firm evidence for the onset of weak static magnetism below T,&. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…We note that the ∆ KT value observed at high temperature is consistent with the one found previously [16,4,5].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…We note that the ∆ KT value observed at high temperature is consistent with the one found previously [16,4,5].…”
supporting
confidence: 80%
“…The increase of ∆ KT detected by the authors of Ref. [16] could be a consequence of a modification of the muon stoping site due to a larger concentration of impurities or defects in the sample.…”
mentioning
confidence: 99%
“…40, but this result has not been reproduced). In the course of a detailed investigation [9] of the evolution of magnetism in U(Pt,Pd) 3 by the µSR technique, we found that LMAF gives rise to a spontaneous µ + precession frequency.…”
Section: Discussionmentioning
confidence: 66%
“…Superconductivity co-exists with antiferromagnetic order. The formation of an antiferromagnetically ordered state below T, = 6 K is revealed by neutron diffraction measurements [3] and supported by muon spin rotation measurements [4]. The uranium moments are oriented along the b-axis of the hexagonal lattice.…”
mentioning
confidence: 94%